2010
DOI: 10.1097/mol.0b013e3283402e9c
|View full text |Cite
|
Sign up to set email alerts
|

Lipid lowering with thyroid hormone and thyromimetics

Abstract: Liver-specific and β-selective thyroid hormone analogs activate a spectrum of favorable thyroid hormone actions that optimize lipid metabolism and promote cholesterol elimination. Further studies should establish long-term safety and potential clinical usefulness of thyromimetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 45 publications
1
56
0
1
Order By: Relevance
“…Furthermore, it is obvious that while the increase in LDL-C with age in males was rather similar to that seen in females, there was no evidence of an increase in PCSK9 in men. Other hormone defi ciencies, such as those of growth hormone ( 15 ) and thyroid hormone ( 26 ), could contribute to the age-dependent reduction of LDLR function and ensuing increase in circulating LDL-C. In particular, the potential role of testosterone (in both genders) still remains to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is obvious that while the increase in LDL-C with age in males was rather similar to that seen in females, there was no evidence of an increase in PCSK9 in men. Other hormone defi ciencies, such as those of growth hormone ( 15 ) and thyroid hormone ( 26 ), could contribute to the age-dependent reduction of LDLR function and ensuing increase in circulating LDL-C. In particular, the potential role of testosterone (in both genders) still remains to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they are powerful agents in counteracting hyperlipidemia and reducing body weight. However, unwanted effects on heart, bone, or muscle restrict their use as therapeutically active compounds for obesity-related diseases (Angelin & Rudling 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of THs in lipids metabolism was first reported in 1930, 1) and since then, accumulating evidence has shown that THs lower cholesterol levels in patients with hypercholesterolemia. [2][3][4] TH synthesis and secretion are strictly regulated by the hypothalamic/pituitary/thyroid (HPT) axis, and their physiological action is modulated via two homologous TH receptors, TRα and TRβ, which belong to the nuclear receptor superfamily of ligand-dependent transcription factors. 5) Because TH receptors are ubiquitously expressed in humans, plasma levels of circulating TH affect various physiological pathways and are associated with a number of pathological states such as hyperthyroidism, which is characterized by decreased serum cholesterol and triacylglycerides (TG) levels, body weight loss, tachycardia, palpitation, muscle wasting, and osteoporosis in postmenopausal women.…”
mentioning
confidence: 99%